Chest radiography in children aged 2-59 months enrolled in the Innovative Treatments in Pneumonia (ITIP) project in Lilongwe Malawi: a secondary analysis - Tisungane Mvalo; Eric D. McCollum; Elizabeth Fitzgerald; Portia Kamthunzi; Robert H. Schmicker; Susanne May; Melda Phiri; Claightone Chirombo; Ajib Phiri; Amy Sarah Ginsburg (BMC, 2022)
Abstract Background Pneumonia is the leading infectious cause of death in children aged under 5 years in low- and middle-income countries (LMICs). World Health Organization (WHO) pneumonia diagnosis guidelines rely on non-specific clinical features. We explore chest radiography (CXR) findings among select children in the Innovative Treatments in Pneumonia (ITIP) project in Malawi in relation to clinical outcomes. Methods When clinically indicated, CXRs were obtained from ITIP-enrolled children aged 2 to 59 months with community-acquired pneumonia hospitalized with treatment failure or relapse. ITIP1 (fast-breathing pneumonia) and ITIP2 (chest-indrawing pneumonia) trials enrolled children with non-severe pneumonia while ITIP3 enrolled children excluded from ITIP1 and ITIP2 with severe pneumonia and/or selected comorbidities. A panel of trained pediatricians classified the CXRs using the standardized WHO CXR research methodology. We analyzed the relationship between CXR classifications, enrollee characteristics, and outcomes. Results Between March 2016 and June 2018, of 114 CXRs obtained, 83 met analysis criteria with 62.7% (52/83) classified as having significant pathology per WHO standardized interpretation. ITIP3 (92.3%; 12/13) children had a higher proportion of CXRs with significant pathology compared to ITIP1 (57.1%, 12/21) and ITIP2 (57.1%, 28/49) (p-value = 0.008). The predominant pathological CXR reading was "other infiltrates only" in ITIP1 (83.3%, 10/12) and ITIP2 (71.4%, 20/28), while in ITIP3 it was "primary endpoint pneumonia"(66.7%, 8/12,; p-value = 0.008). The percent of CXRs with significant pathology among children clinically cured (60.6%, 40/66) vs those not clinically cured (70.6%, 12/17) at Day 14 was not significantly different (p-value = 0.58). Conclusions In this secondary analysis we observed that ITIP3 children with severe pneumonia and/or selected comorbidities had a higher frequency of CXRs with significant pathology, although these radiographic findings had limited relationship to Day 14 outcomes. The proportion of CXRs with "primary endpoint pneumonia" was low. These findings add to existing data that additional diagnostics and prognostics are important for improving the care of children with pneumonia in LMICs. Trial registration ITIP1, ITIP2, and ITIP3 were registered with ClinicalTrials.gov ( NCT02760420 , NCT02678195 , and NCT02960919 , respectively).